Use of complementary and alternative medicine in Germany - a survey of patients with inflammatory bowel disease - Hahn Eckhart G; Szecsenyi Joachim; Rosemann Thomas; Joos Stefanie; Willich Stefan N; Brinkhaus Benno (BMC, 2006)
Abstract Background Previous studies have suggested an increasing use of complementary and alternative medicine (CAM) in patients with inflammatory bowel disease (IBD). The aim of our study was to evaluate the use of CAM in German patients with IBD. Methods A questionnaire was offered to IBD patients participating in patient workshops which were organized by a self-help association, the German Crohn's and Colitis Association. The self-administered questionnaire included demographic and disease-related data as well as items analysing the extent of CAM use and satisfaction with CAM treatment. Seven commonly used CAM methods were predetermined on the questionnaire. Results 413 questionnaires were completed and included in the analysis (n = 153 male, n = 260 female; n = 246 Crohn's disease, n = 164 ulcerative colitis). 52 % of the patients reported CAM use in the present or past. In detail, homeopathy (55%), probiotics (43%), classical naturopathy (38%), Boswellia serrata extracts (36%) and acupuncture/Traditional Chinese Medicine (TCM) (33%) were the most frequently used CAM methods. Patients using probiotics, acupuncture and Boswellia serrata extracts (incense) reported more positive therapeutic effects than others. Within the statistical analysis no significant predictors for CAM use were found. 77% of the patients felt insufficiently informed about CAM. Conclusion The use of CAM in IBD patients is very common in Germany, although a large proportion of patients felt that information about CAM is not sufficient. However, to provide an evidence-based approach more research in this field is desperately needed. Therefore, physicians should increasingly inform IBD patients about benefits and limitations of CAM treatment.